2016
DOI: 10.1080/19440049.2016.1266098
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of plant food supplements and other herbal products containing aristolochic acids using the margin of exposure (MOE) approach

Abstract: After the incidences of induction of aristolochic acid nephropathy after consumption of herbal weight loss preparations that accidentally contained aristolochic acids (AAs), several countries defined national restrictions on the presence of AAs in food, including plant food supplements (PFS) and herbal products. This study investigates whether the risks associated with exposure to AAs via PFS and herbal products are at present indeed negligible. Data reported in literature on AA levels in PFS and other herbal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
1
19
0
5
Order By: Relevance
“…Previous studies have reported that AA exerts therapeutic effects, including antitumour, anti‐infective, anti‐inflammatory, analgesic, antifertility and blood pressure‐regulatory effects. Thus, AA has been commonly used to treat a variety of illnesses, such as eczema, pneumonia, stroke, hepatitis, snake bites, arthritis, gout and coronary artery diseases, and is widely used in traditional and local medicines and herbal products . Aristolochia fangchi , but not Stephania tetrandra , contains AA.…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported that AA exerts therapeutic effects, including antitumour, anti‐infective, anti‐inflammatory, analgesic, antifertility and blood pressure‐regulatory effects. Thus, AA has been commonly used to treat a variety of illnesses, such as eczema, pneumonia, stroke, hepatitis, snake bites, arthritis, gout and coronary artery diseases, and is widely used in traditional and local medicines and herbal products . Aristolochia fangchi , but not Stephania tetrandra , contains AA.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…In addition to differences in the accumulated dose of AA and the duration of AA intake, individual differences in the activities of enzymes that catalyse the biotransformation of AA could be responsible for the observed discrepancy in susceptibility levels. Thus, the identification of the enzymes involved in AA metabolism is of particular relevance . In the liver, the AA mixture is metabolized under anaerobic conditions to the corresponding aristolactam I and II, whereas under aerobic conditions, the only metabolite obtained is the O‐demethylated derivative aristolochic acid Ia (AA Ia), which is a biotransformation product from aristolochic acid I (AA I).…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…Devido essas informações, a Agência Européia de Medicamento vem proibindo a comercialização de produtos à base de plantas que sabidamente contém estes ácidos aristolóquicos(RAUBER, 2006). Além disso, a agência Americana Food and Drug Administration (FDA) vem advertindo consumidores em relação a continuidade do uso de produtos que contenham ácidos aristolóquicos(TABACH et al, 2013;ROZAINI ABDULLAH et al, 2017). Nesse estudo, o extrato da planta reduziu 20 significativamente o tempo de crise epilética em todos os tempos analisados (24, 48 e 72 horas após a administração da solução).…”
unclassified